Analisis Efisiensi Pemasaran Jamur Tiram Putih (Pleurotus Ostreatus) di Kelurahan Air Rambai Kecamatan Curup Kabupaten Rejang - Fahrozi Fahrozi; Febri Nur Pramudya; Mira Yanuarti (Jurnal Riset Rumpun Ilmu Tanaman, 2024)
Research on marketing efficiency analysis of white oyster mushrooms (Pleurotus Ostreatus) in Air Rambai Village, Curup District, Rejang Lebong Regency aims to determine marketing channels, and analysis of marketing margins, as well as to determine whether the marketing efficiency of white oyster mushrooms in Air Rambai Village, Curup District.This research was conducted in March 2022 in Air Rambai Village, Curup District, Rejang Lebong Regency with farmers in Air Rambai Village. Data analysis used in this research is marketing channel analysis, marketing margin analysis, and marketing efficiency analysis. This data analysis was used for farmers and the 12 retailer respondents in Air Rambai Village, Curup District, Rejang Lebong Regency.Based on the results of data analysis, it can be seen that the marketing channel of white oyster mushrooms in Air Rambai Village, Curup District, Rejang Lebong Regency has two marketing channel patterns where the first marketing channel pattern sells white oyster mushrooms directly to end consumers, and the second marketing channel pattern is farmers sell to traders. retailers and then traders resell to final consumers. The marketing margin in the first marketing channel is Rp. 0, while in the second marketing channel it is Rp. 11,583. and the marketing efficiency of white oyster mushrooms in Air Rambai Village, Curup District, Rejang Lebong Regency is said to be efficient.